Фразеологічні одиниці з компонентом-антропонімом - Пелипась, М. (Культура слова, 2021)
У статті досліджено фразеологічні одиниці з компонентом-антропонімом. Вирізнено за походженням основні групи
ФО, які утворюють мікросистему ФО з компонентом-антропонімом, здійснено семантичну характеристику таких
одиниць. Зазначено, що абсолютна більшість ФО з компонентом-антропонімом пов’язана з описом людини, рис її характеру, психічних процесів, дій і станів. Чимало ФО також позначають абстрактні поняття й різноманітні ситуації. Тільки
окремі ФО цієї мікросистеми характеризують матеріальне
становище людини, її поведінку, вчинки тощо.
Проведено структурно-синтаксичний аналіз ФО з компонентом-антропонімом. Констатовано, що більшість ФО цієї
мікросистеми структурно оформлені як словосполучення з
підрядним чи сурядним зв’язком. Описано структурні моделі
ФО з компонентом-антропонімом. Зазначено, що для ФО цієї
мікросистеми варіантність здебільшого не характерна. The article is dedicated to the study of phraseological units with
an anthroponym component in the Ukrainian language. In particular,
it is noted that this phraseological microsystem was never studied
within the Ukrainian language as a separate subject, but only in
conjunction with studying phraseological units with a proper name
component in general.
The analysis carried out makes it possible to single out three main
groups of phraseological units with an anthroponym component
depending on origin: 1) those with commonly used anthroponyms,
male names in most cases; 2) those with anthroponyms of biblical
origin; and 3) those with anthroponyms of mythological origin.
On the basis of semantic features, nine most essential
groups were identified in this phraseological microsystem. It is
emphasized that the absolute majority of phraseological units with
an anthroponym component are associated with a description of a
person, his character traits, mental processes, actions and states, etc.
A significant part of the phraseological units within this microsystem
characterize abstract concepts and various situations, and only a
small number of them are used to designate material merits or, vice
versa, shortcomings of a person, his behavior, actions, etc.
A structural-syntactic analysis of phraseological units with an
anthroponym component is also carried out. It is stated that in
terms of structure, the lion’s share of phraseological units of this
microsystem correspond to a word combination with a subordinate
connection to a greater extent, and with a coordinative connection to
a lesser extent. A part of phraseological units with an anthroponym
component also correspond to a combination of words, a common
figure of speech and a subordinate clause of a complex sentence. The
models used to construct phraseological units with an anthroponym
component are described in detail.
The factual phraseological material indicates that variance
is a nontypical phenomenon for the phraseological units of the
analyzed microsystem, especially for phraseological units with an
anthroponym component of biblical origin and the same units of
mythological origin.